Conflict : what has religion got to do with it? : an African-European dialogue. - Goethe-Institut (Accra, Ghana); International Conference on Conflict and Religion (2003 : Accra, Ghana) (Accra : Woeli Pub. Services : Goethe-Institut Accra, 2004)
Lectures and presentations from an international conference on the topic of conflict and religion, which took place in October 2003 and was organized by the Goethe-Institut Accra in co-operation with the Accra Daily Mail.
Human rights and religion : the Christian perspective / Emile Francis Shari (p. 93-102). -- Human rights and religion / Mohammed Halrib (p. 103-113). -- Religion and conflict : synonymous or paradoxical? / Charles Palmer-Buckle (p. 114-124). -- Islam in a post-colonial and conflict-free Ghana : challenges or equilibrium / Mahmoud M Gedci (p. 127-150). -- Islam in post-colonial West African christianized countries / Mensa Obabi (p. 151-156). -- Muslim's communities in multi-religious milieux : some reflections on the Madman Constitution / Samusis Iunido Samusi (p. 159-180). -- Sharia and secular constitutions / Franz Kogelmann (p. 181-192). -- Conflicts -- a perspective on the religious dimensions of the problem / Sheikh J.C Omaye (p. 195-201). -- Instrumentalizing religion in the contest for political power / Georg Brunold (p. 202-208). -- Must the Church involve herself in politics? / Peter K Servong (p. 209-215). -- r (p. 216-224). -- Cultural pluralism, religion and educational philosophy / George P Hagan (p. 227-236). -- Educational systems and the influence of religion / Mauloi Adam (p. 237-241).
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Social conflict -- Religious aspects -- Congresses; Culture conflict -- Religious aspects -- Congresses; Ethnic conflict -- Religious aspects -- Congresses; Afrika; Accra <2004>; Kongress -- Accra -- 2003.; Conference papers and proceedings; Accra (2003)